Preparation method of positive electrode slurry, positive electrode slurry, positive electrode and lithium battery

By using technical means such as modified glue solution and multi-copolymer in the positive electrode slurry, the problem of insufficient capacity and easy layering of the lithium-rich manganese-based positive electrode water slurry is solved, and higher battery performance and stability are achieved.

CN119517939APending Publication Date: 2025-02-25XI GU (ZHE JIANG) KE JI YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411579814.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The lithium-rich manganese-based positive electrode water slurry is insufficient in the capacity and is easy to delaminate after long-term placement.

Method used

Using a method of preparing a positive electrode slurry, a first reagent (sodium carboxymethylcellulose, lithium carboxymethylcellulose or polyacrylamide) and a second reagent (conductive carbon black, aqueous carbon nanotubes, etc.) are mixed with deionized water to form a modified gel solution, and mixed with a positive electrode powder, a pH adjuster and acrylate-based multi-copolymer to form a stable positive electrode slurry.

Benefits of technology

The dispersion stability of the positive electrode slurry is improved, the stability of the positive electrode structure is enhanced, the capacity, magnification and circulation performance of the battery are improved, and the occurrence of stratification phenomenon is slowed down or suppressed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517939A_ABST
    Figure CN119517939A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of positive electrode slurry, the positive electrode slurry, a positive electrode and a lithium battery, and the preparation method comprises the following steps: mixing a first reagent, a second reagent and deionized water to form a modified glue solution, the second reagent is one or a mixture of more of conductive carbon black, conductive graphite, ketjen black, carbon nanofibers, water-based carbon nanotubes and graphene; and at least mixing positive electrode powder, a pH regulator and the modified glue solution to form the positive electrode slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and particularly to a method for preparing a positive electrode paste, a positive electrode paste, a positive electrode and a lithium battery. Background Art

[0002] The lithium-rich manganese-based cathode material (LRMO, xLi2MnO3·(1-x)LiTMO2 [0<x<1, TM = Ni, Co, Mn]) has the advantages of high specific capacity, high energy density, environmental protection and low cost, and is regarded as a candidate for the new generation of lithium-ion battery cathode materials with great commercial prospects, and is expected to be applied to the fields of medium and high-end 3C and power batteries.

[0003] The lithium-rich manganese-based cathode (LRMO) paste is mainly divided into an oil-based paste and an aqueous paste. Among them, the aqueous paste is mainly composed of a positive electrode active material, a conductive agent, a thickener, a binder, and an acidic agent. The main problem of the aqueous paste is that the acidic agent will damage the configuration of the positive electrode active material, which not only causes the decrease of the specific capacity of the positive electrode active material per gram, but also causes the decrease of the viscosity of the aqueous paste and is easy to stratify after long-term storage. Summary of the Invention

[0004] Based on this, in view of the problems of insufficient specific capacity of the aqueous lithium-rich manganese-based cathode paste and easy stratification after long-term storage, it is necessary to provide a method for preparing a positive electrode paste, a positive electrode paste, a positive electrode and a lithium battery.

[0005] The technical solution provided by the present invention is as follows: A method for preparing a positive electrode paste, comprising: Mixing a first reagent, a second reagent and deionized water to form a modified glue solution, wherein the first reagent is one or a mixture of several of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and polyacrylamide, and the second reagent is one or a mixture of several of conductive carbon black, conductive graphite, Ketjen black, carbon nanofibers, aqueous carbon nanotubes and graphene; Mixing at least a positive electrode powder, a pH regulator and the modified glue solution to form a positive electrode paste.

[0006] The pH regulator of the present invention is one or a mixture of several of oxalic acid, citric acid, acetic acid, succinic acid, glycine, butanetetracarboxylic acid, phosphoric acid, boric acid and carbonic acid.

[0007] The positive electrode paste of the present invention is further mixed with an acrylate-based multi-component copolymer.

[0008] The preparation steps of the modified glue solution of the present invention sequentially include: Step S1: Mixing the first reagent and deionized water to form a first solution; Step S2: Adding the second reagent to the first solution to form the modified glue solution; The steps of preparing the positive electrode slurry sequentially include: Step S3: adding the positive electrode powder to the modified glue to form a first mixed slurry; Step S4: adding deionized water to the first mixed slurry to form a second mixed slurry; Step S5: adding the pH regulator to the second mixed slurry to form a third mixed slurry; Step S6: adding the acrylic acid ester multi-polymer to the third mixed slurry to form the positive electrode slurry.

[0009] The present invention is calculated by mass: Positive electrode powder, 93 parts to 94.5 parts; First reagent, 1-2 parts; The second reagent, 2.5-3.5 parts; Acrylic acid ester multipolymer, 2-3 parts; pH adjuster, 0.5-1.2 parts; Deionized water, 20-60 parts in total in step S1 and step S4.

[0010] The first reagent of the present invention is sodium carboxymethyl cellulose, the second reagent is a mixture of conductive carbon black and water-based carbon nanotubes, and the pH regulator is phosphoric acid; By mass: Positive electrode powder, 93.5 parts; Conductive carbon black, 2.5 parts; Water-based carbon nanotubes, 0.5 parts; Sodium carboxymethyl cellulose, 1 part; Acrylate multipolymer, 2.5 parts; Phosphoric acid, 0.65 parts.

[0011] In step S6 of the present invention, the pH of the positive electrode slurry is 7.5-8.5.

[0012] A positive electrode slurry is prepared by adopting the preparation method.

[0013] A positive electrode is obtained by coating the positive electrode slurry on a substrate and then drying it.

[0014] A lithium battery comprises the positive electrode.

[0015] The beneficial effects of the present invention are: Sodium carboxymethyl cellulose, lithium carboxymethyl cellulose or polyacrylamide has both hydrophobic groups and hydrophilic groups. This property enables the first agent to help the second agent and the positive electrode powder to disperse in the positive electrode slurry. The positive electrode slurry can maintain a stable dispersion state for a long time, slowing down or inhibiting the occurrence of positive electrode slurry stratification.

[0016] In particular, the carboxyl group of sodium carboxymethyl cellulose can form hydrogen bonds with the hydroxyl groups on the surface of the positive electrode powder, thereby improving the bonding force between the positive electrode slurry and the substrate and reducing the occurrence of material falling after the positive electrode slurry is dried. In addition, the first reagent improves the stability of the positive electrode powder in the positive electrode slurry, which also helps to improve the gram capacity, rate and cycle performance of the battery.

[0017] In summary, the first reagent of the present invention has the triple effects of improving the dispersion stability of the positive electrode slurry, improving the stability of the positive electrode structure and improving the battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The charge and discharge rate test curves in Example 2, Comparative Example 1 and Comparative Example 2 of the present invention are shown; Figure 2 The charge-discharge cycle test curves in Example 2, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 3 The EIS impedance spectra of Example 2, Comparative Example 1 and Comparative Example 2 of the present invention are shown. DETAILED DESCRIPTION

[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0020] Embodiment 1: This embodiment provides a positive electrode slurry, and the preparation method thereof comprises the following steps in sequence (all parts are calculated by mass): Step S1: Mix a first reagent with deionized water to form a 1.8 wt % first solution.

[0021] In this embodiment, the first reagent is sodium carboxymethyl cellulose, and the first reagent has a total of 1 part.

[0022] Step S2: Add the second reagent to the first solution, stir at 500 rpm for 10 min, and then stir at 2000 rpm for 45-60 min to form a modified glue solution.

[0023] In this embodiment, the second reagent is conductive carbon black, and the second reagent has a total of 2.5 parts.

[0024] Step S3: Add the positive electrode powder to the modified glue solution, stir at 500 rpm for 10 min, and then stir at 2500 rpm for 90-120 min to form a first mixed slurry.

[0025] In this embodiment, the positive electrode powder is LRMO (Li 1.21 Ni 0.136 Co 0.133 Mn 0.52 O2), a total of 94.5 parts of positive electrode powder.

[0026] Step S4: adding deionized water to the first mixed slurry, stirring at 2500 rpm for 30 min, to form a second mixed slurry with a solid content of 50%-75%.

[0027] Step S5: Add a pH adjuster to the second mixed slurry, and stir at 1500 rpm for 15 min to form a third mixed slurry with a pH of 8-9.

[0028] In this embodiment, the pH adjuster is phosphoric acid, and the pH adjuster is 0.5 parts in total.

[0029] Step S6: Add the acrylic acid ester multi-polymer to the third mixed slurry, and stir at 1000-2000 rpm for 30 min to form a positive electrode slurry with a pH of 7.5-8.5.

[0030] In this embodiment, the acrylic acid ester multi-polymer contains 2 parts in total.

[0031] Step S7: The viscosity of the positive electrode slurry is adjusted to 4000-6000 mPa·s, vacuum degassed and sieved with a 120-mesh screen.

[0032] The ambient temperature in steps S1 to S7 is between 15°C and 28°C.

[0033] A portion of the positive electrode slurry processed in step S7 was placed in a 250 mL beaker for stability evaluation.

[0034] The remaining positive electrode slurry treated in step S7 is coated on both sides of a 16 μm thick substrate (aluminum foil current collector), and the coating double-sided surface density is not less than 20 mg / cm 2 , coating speed 3m / min, drying at 65℃-115℃ and then rolling to obtain a positive electrode with a single-sided coating thickness of about 50μm.

[0035] Cut a part of the prepared positive electrode into long strips (length 100mm * width 25mm), then take a stainless steel plate with a width of 50mm, stick 3M double-sided tape (length 10mm * width 25mm) on its bright surface, then stick the cut positive electrode on one side on the 3M double-sided tape, and use a pressure roller to roll back and forth on the positive electrode surface 3 times. Finally, fix the sample on the tensile machine and load it at a speed of 250mm / min until the positive electrode is completely peeled off, stop the test, take 5 samples each time, and record the average peeling force. The appearance of the electrode is described by naked eye observation.

[0036] The remaining positive electrodes were further processed into CR2032 button batteries, in which the negative electrodes were made of metal lithium sheets. The Xinwei battery test system was used for room temperature charge and discharge tests, and the test voltage range was 2.0V-4.7V. In addition, the electrochemical workstation was used to perform electrochemical alternating current impedance (EIS) tests on the CR2032 button batteries, with a frequency range of 0.01Hz-1MHz and a sinusoidal AC voltage disturbance signal amplitude of 5mV. Embodiment 2: The difference between this embodiment and embodiment 1 is that the composition and measurement of each raw material in the process of preparing the positive electrode slurry have changed. Specifically: The positive electrode powder is LRMO, and the positive electrode powder totals 93.5 parts.

[0037] The second reagent is a mixture of conductive carbon black and water-based carbon nanotubes, wherein the conductive carbon black is 2.5 parts and the water-based carbon nanotubes is 0.5 parts.

[0038] The first reagent is sodium carboxymethyl cellulose, and the first reagent has a total of 1 part.

[0039] The acrylic acid ester multi-polymer is 2.5 parts in total.

[0040] The pH adjuster was phosphoric acid, and the total amount of the pH adjuster was 0.65 parts.

[0041] Embodiment 3: The difference between this embodiment and embodiment 1 is that the composition and measurement of each raw material in the process of preparing the positive electrode slurry have changed. Specifically: The positive electrode powder is LRMO, and there are 94 parts of positive electrode powder in total.

[0042] The second reagent is a mixture of conductive carbon black and water-based carbon nanotubes, wherein the conductive carbon black is 2.0 parts and the water-based carbon nanotubes are 0.5 parts.

[0043] The first reagent is sodium carboxymethyl cellulose, and the first reagent has a total of 1 part.

[0044] The acrylic acid ester multi-polymer is 2.5 parts in total.

[0045] The pH adjuster is phosphoric acid, and the pH adjuster is 1 part in total.

[0046] Embodiment 4: The difference between this embodiment and embodiment 1 is that the composition and measurement of each raw material in the process of preparing the positive electrode slurry have changed. Specifically: The positive electrode powder is LRMO, and there are 94 parts of positive electrode powder in total.

[0047] The second reagent is a mixture of conductive carbon black and water-based carbon nanotubes, wherein the conductive carbon black is 2.5 parts and the water-based carbon nanotubes is 0.5 parts.

[0048] The first reagent is sodium carboxymethyl cellulose, and the first reagent has a total of 1 part.

[0049] The acrylic acid ester multi-polymer is 2 parts in total.

[0050] The pH adjuster was oxalic acid, and the total amount of the pH adjuster was 0.5 parts.

[0051] Embodiment 5: The difference between this embodiment and embodiment 1 is that the composition and measurement of each raw material in the process of preparing the positive electrode slurry have changed. Specifically: The positive electrode powder is LRMO, and the positive electrode powder totals 93.5 parts.

[0052] The second reagent is a mixture of conductive carbon black and water-based carbon nanotubes, wherein the conductive carbon black is 2.5 parts and the water-based carbon nanotubes is 0.5 parts.

[0053] The first reagent is sodium carboxymethyl cellulose, and the first reagent has a total of 1 part.

[0054] The acrylic acid ester multi-polymer is 2.5 parts in total.

[0055] The pH adjuster was oxalic acid, and the total amount of the pH adjuster was 0.8 parts.

[0056] Embodiment 6: The difference between this embodiment and embodiment 1 is that the composition and measurement of each raw material in the process of preparing the positive electrode slurry have changed. Specifically: The positive electrode powder is LRMO, and there are 93 parts of positive electrode powder in total.

[0057] The second reagent is a mixture of conductive carbon black and water-based carbon nanotubes, wherein the conductive carbon black is 3.0 parts and the water-based carbon nanotubes is 0.5 parts.

[0058] The first reagent is sodium carboxymethyl cellulose, and the first reagent is 0.5 parts in total.

[0059] The acrylic acid ester multi-polymer is 3 parts in total.

[0060] The pH adjuster was phosphoric acid, and the total amount of the pH adjuster was 0.65 parts.

[0061] Embodiment 7: The difference between this embodiment and embodiment 1 is that the composition and measurement of each raw material in the process of preparing the positive electrode slurry have changed. Specifically: The positive electrode powder is LRMO, and there are 93 parts of positive electrode powder in total.

[0062] The second reagent is a mixture of conductive carbon black and water-based carbon nanotubes, wherein the conductive carbon black is 3.0 parts and the water-based carbon nanotubes is 0.5 parts.

[0063] The first reagent is sodium carboxymethyl cellulose, and the first reagent has a total of 1 part.

[0064] The acrylic acid ester multipolymer was replaced by an acrylonitrile multipolymer, and the acrylonitrile multipolymer accounted for 2.5 parts in total.

[0065] The pH adjuster was phosphoric acid, and the total amount of the pH adjuster was 1.2 parts.

[0066] Embodiment 8: The difference between this embodiment and embodiment 1 is that the composition and measurement of each raw material in the process of preparing the positive electrode slurry have changed. Specifically: The positive electrode powder is LRMO, and there are 93 parts of positive electrode powder in total.

[0067] The second reagent is a mixture of conductive carbon black and water-based carbon nanotubes, wherein the conductive carbon black is 2.5 parts and the water-based carbon nanotubes is 0.5 parts.

[0068] The first reagent is sodium carboxymethyl cellulose, and the first reagent has a total of 1 part.

[0069] The acrylic acid ester multipolymer was replaced by an acrylonitrile multipolymer, and the acrylonitrile multipolymer was 3 parts in total.

[0070] The pH adjuster was oxalic acid, and the total amount of the pH adjuster was 1.0 part.

[0071] Comparative Example 1: The difference between this comparative example and Example 2 is that the execution order of step S5 and step S6 is swapped.

[0072] Comparative Example 2: The difference between this comparative example and embodiment 3 is that the execution order of step S6 is between steps S1 and S2.

[0073] In Examples 1 to 8, and Comparative Examples 1 and 2, the stability test data of the positive electrode slurry are shown in Table 1.

[0074] Table 1

[0075] First, among Examples 1 to 8, only the positive electrode slurry of Example 6 gradually decreased in viscosity and produced stratification within 20 hours. The main reason is that the types and proportions of reagents in its preparation process are different from those in Examples 1 to 5, Example 7 and Example 8. The most likely reason is that the content of the first reagent, sodium carboxymethyl cellulose, is too low. It can be seen that sodium carboxymethyl cellulose is most likely used as a thickener in the positive electrode slurry.

[0076] It is particularly noteworthy that in Example 1, Example 3-Example 5, Example 7 and Example 8, the viscosity of the positive electrode slurry is always gradually increasing within 20 hours. Among them, the viscosity value of the positive electrode slurry in Example 3-Example 5 increases relatively slowly, and the viscosity value of the positive electrode slurry in Example 1, Example 7 and Example 8 increases very rapidly. However, due to the above-mentioned viscosity increase characteristics, although the occurrence of the positive electrode slurry stratification phenomenon is suppressed, it also leads to the problem that the viscosity value stability of the positive electrode slurry in Example 1, Example 3-Example 5, Example 7 and Example 8 is insufficient.

[0077] In contrast, in Example 2, although the viscosity of the positive electrode slurry does not increase all the time, in other words, the ability to suppress stratification is inferior to that of other examples, it still suppresses stratification normally, and the stability of its viscosity value is significantly better than that of other examples, which plays a crucial role in ensuring the stability of the surface density during the coating process and then stabilizing the final battery performance.

[0078] It is not difficult to see that Example 2 is the optimal example. While ensuring that the positive electrode slurry does not stratify, the viscosity of the positive electrode slurry can be maintained in the most stable state, thereby ensuring better consistency in performance between different batches of batteries.

[0079] By comparing Example 7 and Example 8 with Example 2, it can be seen that the main difference is that the acrylic acid ester multipolymer is replaced by an acrylonitrile multipolymer. It can be seen that the acrylonitrile multipolymer can also act as a thickener in the positive electrode slurry, and its thickening effect will obviously destroy the viscosity stability of the positive electrode slurry.

[0080] Comparing Comparative Example 1 with Example 2, it can be seen that phosphoric acid reacts with the positive electrode powder before the acrylic ester copolymer, which is crucial for the anti-stratification ability of the positive electrode slurry. The reason is probably that phosphoric acid will first undergo a neutralization reaction, so that lithium and transition metal phosphates are formed in situ on the surface of the positive electrode powder. After the acrylic ester copolymer is subsequently added, the hydroxyl groups in the lithium and transition metal phosphates can form hydrogen bonds through the carboxyl groups in the acrylic ester copolymer to inhibit the dissociation and side reactions of lithium and transition metal phosphates, thereby inhibiting the Li + / H +The proton exchange reaction prevents the increase of pH and maintains the storage stability of the slurry. At the same time, sodium carboxymethyl cellulose will also cross-link with the acrylic ester multipolymer to further improve the stability of the positive electrode slurry.

[0081] On the contrary, if the acrylic ester copolymer contacts the positive electrode powder before phosphoric acid, the acrylic ester copolymer will first coat the positive electrode powder, resulting in the positive electrode powder being unable to contact normally with the phosphoric acid, and thus the aforementioned process cannot be achieved normally, and the slurry viscosity cannot be effectively improved.

[0082] Comparing Comparative Example 2 with Example 3, similar conclusions can be found, which further enhances the credibility of the above conclusion, that is, phosphoric acid needs to react with the positive electrode powder before the acrylic acid ester multi-polymer.

[0083] In Examples 1 to 8, and Comparative Examples 1 and 2, the stripping performance tests of the positive electrodes are shown in Table 2.

[0084] Table 2

[0085] It is not difficult to find that in Examples 1 to 8, the peeling force of the positive electrode is significantly better than that of Comparative Examples 1 and 2. Among them, the peeling force corresponding to Example 2 is the largest, and in Examples 4, 7 and 8, the anti-peeling ability of the positive electrode is still insufficient. This proves that Example 2 is also the best example in terms of anti-peeling ability, which can effectively improve the processability and yield of the positive electrode, improve the cycle stability of the final battery, and reduce the risk of self-discharge.

[0086] In Examples 1 to 8, and Comparative Examples 1 and 2, the electrical performance test results of the batteries are shown in Table 3.

[0087] Table 3

[0088] See also Figure 1 , Figure 2 As shown in Table 3, in Examples 1 to 8, the first discharge gram capacity, first efficiency, rate performance and cycle capacity are significantly better than those in Comparative Examples 1 and 2, and in Examples 1 to 8, the battery electrical properties in Example 2 are still the best at the same time, and the battery in Example 2 shows lower charge transfer impedance and better ion conductivity. It can be seen that Example 2 can simultaneously meet the optimal requirements of positive electrode slurry anti-delamination ability, positive electrode anti-stripping ability, battery electrical performance and battery stability.

[0089] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0090] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a positive electrode slurry, characterized in that: include: The first reagent, the second reagent and deionized water are mixed to form a modified glue solution, wherein the first reagent is one or a mixture of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and polyacrylamide, and the second reagent is one or a mixture of conductive carbon black, conductive graphite, Ketjen black, nanocarbon fiber, water-based carbon nanotube and graphene; At least the positive electrode powder, the pH regulator and the modified glue are mixed to form a positive electrode slurry.

2. The method for preparing the positive electrode slurry according to claim 1, characterized in that: The pH regulator is one of oxalic acid, citric acid, acetic acid, succinic acid, glycine, butanetetracarboxylic acid, phosphoric acid, boric acid and carbonic acid, or a mixture of several of them.

3. The method for preparing the positive electrode slurry according to claim 1, characterized in that: The positive electrode slurry is also mixed with an acrylic acid ester multi-polymer.

4. The method for preparing the positive electrode slurry according to claim 3, characterized in that: The preparation steps of the modified glue solution include: Step S1: mixing the first reagent with deionized water to form a first solution; Step S2: adding the second reagent to the first solution to form the modified glue solution; The steps of preparing the positive electrode slurry sequentially include: Step S3: adding the positive electrode powder to the modified glue to form a first mixed slurry; Step S4: adding deionized water to the first mixed slurry to form a second mixed slurry; Step S5: adding the pH regulator to the second mixed slurry to form a third mixed slurry; Step S6: adding the acrylic acid ester multi-polymer to the third mixed slurry to form the positive electrode slurry.

5. The method for preparing the positive electrode slurry according to claim 4, characterized in that: By mass: Positive electrode powder, 93 parts to 94.5 parts; First reagent, 1-2 parts; The second reagent, 2.5-3.5 parts; Acrylic acid ester multipolymer, 2-3 parts; pH adjuster, 0.5-1.2 parts; Deionized water, 20-60 parts in total in step S1 and step S4.

6. The method for preparing the positive electrode slurry according to claim 5, characterized in that: The first reagent is sodium carboxymethyl cellulose, the second reagent is a mixture of conductive carbon black and water-based carbon nanotubes, and the pH regulator is phosphoric acid; By mass: Positive electrode powder, 93.5 parts; Conductive carbon black, 2.5 parts; Water-based carbon nanotubes, 0.5 parts; Sodium carboxymethyl cellulose, 1 part; Acrylate multipolymer, 2.5 parts; Phosphoric acid, 0.65 parts.

7. The method for preparing positive electrode slurry according to claim 4, characterized in that: In step S6, the pH of the positive electrode slurry is 7.5-8.

5.

8. A positive electrode slurry, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 7.

9. A positive electrode, characterized in that The positive electrode slurry as claimed in claim 8 is coated on a substrate and then dried.

10. A lithium battery, characterized in that: Comprising the positive electrode as claimed in claim 9.